Nappe tectonics in the Matomb-Hegba area, South-Central Cameroon: Implications on the tectonic evolution of the Yaoundé Group in the Central African Orogenic Belt - Victor Metang; Henri Appolinaire Kenzo; Rose Noel Ngo Belnoun; Dior-Christelle Mboutchouang; Steve Franck Bamou-Wandji; Brigitte Domkam; Boris Toyi Tchouta (Geosystems and Geoenvironment)
This paper documents the thrust tectonics in the Yaoundé Group using detailed field mapping and satellite imagery data. The litho-stratigraphic of the Matomb-Hegba area located W of the Pan-African Yaoundé series comprised two main metasedimentary units: (1) garnet-kyanite migmatites at the top, dated at 622 ± 43 Ma, and (2) garnet-rutile micaschists at the bottom, with ages ranging between 546 and 604 Ma. The contact between the two lithological units is materialized by a ductile shear zone evidenced by structural and remote sensing data: inversion of the foliation at the contact of the shear zone, P2 folds with southern vergence, E-W to NE-SW sinistral shear planes, uniform dip (towards the SE) and several criteria indicating a sinistral and dextral kinematics respectively in light grey mylonites and in dark grey mylonites along the ductile shear zone. During D2 deformation stage, subhorizontal S2 foliation associated to NE-SW Lm2 mineral lineations were developed in garnet-kyanite migmatites. The thrusting contact zone is characterized by mylonitized micaschists (light grey mylonites) and migmatites (dark grey mylonites) separated by talcschist and amphibolite boudins which would have served as a ‘‘soap layer’’ leading to the slipping of garnet-kyanite migmatites over garnet-rutile micaschists. The disposition of garnet-kyanite migmatites (sometimes outcrop in the form of klippes) over garnet-rutile micaschists, the presence of a ductile shear zone at the contact of the two lithological units, and the NE-SW mineral lineation suggest the existence of at least two tectonic nappes (garnet-kyanite migmatites and garnet-rutile micaschists) with NE-SW-trends in the Yaoundé Group. This nappe disposition induced by ductile shear corroborates well with the compressive shear tectonics as described in the NE of Brazil and in the northern and eastern part of the Saharan Block.